Giocare al fort/da. Lacan, Derrida, e la pulsione di morte - Moroncini, Bruno (Bollettino Filosofico, 2021)
The essay discusses the relationship between deconstruction and psychoanalysis through the reconstruction of the different interpretations of the Freudian text Beyond the Pleasure Principle developed by Jacques Lacan in his seminar on the ethics of psychoanalysis in 1959-1960 and Jacques Derrida in his seminar on “Life and Death” in 1975. If for Lacan the death drive does not concern the phenomenon of natural life but of linguistic and historical life and implies a critique of Darwin’s evolutionary theory, for Derrida the most relevant effect of Freud’s essay is the indetermination of the life-death difference and Freud’s abandonment of any scientific and philosophical logic in favour of a form of “speculation” that is the premise of the method of deconstruction. Keywords: Death Drive, Deconstruction, Derrida, Freud, Lacan